BNT162b2 COVID-19 Vaccine Induced Immune Thrombocytopenic Purpura - A. K. Ghosh; S. Bhushan; L. D. R. Lopez; D. Sampat; Z. Salah; C. A. Hatoum (Case Reports in Medicine)
Immune thrombocytopenic purpura (ITP) has been reported following vaccinations such as MMR as well as after viral infections such as hepatitis C and HIV. Few case reports have been reported of ITP after COVID-19 infections and COVID-19 vaccines. Herein, we present a patient who presented with severe ITP with a platelet count of 0 after receiving the second dose of the BNT162b2 mRNA COVID-19 vaccine (also known as the Pfizer BioNTech). She subsequently recovered with a prolonged treatment course.